Re-engineering the Cypriot General Healthcare System for Syndemics - Sarah Cuschieri; Amalia Hatziyianni; Peter Karayiannis; Juanita A. Haagsma; Grant M. A. Wyper; Marios Kantaris; Mamas Theodorou; Elena Pallari (Frontiers Media S.A., 2022)
To date in Cyprus, there is no dedicated "Quality Improvement" body or Public Health authority. The long-awaited general healthcare system (known as GeSy or GHS) has been completed, mid-stream of the COVID-19 pandemic. A recently proposed resilience plan in response to the lessons learnt from the pandemic was put forward by the Government of the Republic of Cyprus to strengthen the capacity of the GHS and support public health defense. The negotiator of GeSy and Health Minister 2015-2018 also provided his view that the health system needs a holistic transformation of service provision. Recognizing failures and thinking from a syndemogenesis perspective how the envisioned patient-centric healthcare delivery can be achieved, we propose that the public health response could also be linked to a politico-economic one in shielding GeSy. We make such case for a syndemic strategy (simultaneous management of COVID-19 and pre-existing epidemics on the island) and the development of the five-district model where each main district hospital is to complement the activities of the GHS through developing: 1. A training Center for training and sharing of best practices for COVID-19 and other public emergencies. 2. A public health body. 3. A quality improvement institute. 4. A commissioning center on planning and streamlining healthcare services. 5. A clinical trial platform. The rationale is based on the management literature and use of existing resources and capabilities for transforming the GeSy and generating value.